Impact of Radix-10 Redundant Digit Set [−6, 9] on Basic Decimal Arithmetic Operations - Jaberipur, Ghassem; Ghazanfari, Farzad (IEEE transactions on very large scale integration (VLSI) systems, 2022)
Redundant-digit decimal computer arithmetic, with the principal property of carry-free addition, has been the subject of several studies, as the relevant literature contains a wide variety of decimal digit sets and their binary representations. For example, symmetric decimal signed digit sets [-\alpha, \alpha] , for \alpha \in \{5,6,7,8,9 \} , and the asymmetric ones, such as [−8, 9], [−9, 7], and [0, 15], have been the basis of variant hardware architectures for decimal arithmetic operations. However, digit sets with the minimal 4-bit representations show better figures of merit. In this work, we present a new decimal digit set [−6, 9], called diminished-6 overloaded decimal digit set (DODDS). Its special 4-bit representation contains two posibits (weighted 2^{3} and 2^{0} ) and two negabits (weighted 2^{2} and 2^{1} ). Design and implementation of the corresponding carry-free decimal adders and subtractors are thoroughly discussed. Furthermore, to cover the requirements of all possible DODDS applications in decimal multipliers, dividers, and square rooters, we provide adder/subtractor designs for a variety of input combinations of DODDS and binary coded decimal (BCD) operands, all with DODDS output (e.g., DODDS + BCD = DODDS, which is useful in BCD partial product reduction). Analytical and synthesis-based evaluations and comparisons with similar previous works show the notable merits of DODDS over the other redundant decimal digit sets.